2016
DOI: 10.5455/medarh.2016.70.66-68
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Osteoporosis and Calcium Urolithiasis in Adult Population

Abstract: Introduction:Scientific studies indicate that there is a correlation between decreased bone mineral density and the age of the patient, especially in post menopausal women.Goal:The aim of our study was to assess the connection between osteoporosis and the age of respondents, based on the DEXA findings in patients with calcium urolithiasis.Material and methods:The study was prospectively and conducted in University Clinical Center Banja Luka, at the Urology Clinic and Clinic of Internal Medicine. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…A retrospective study of 57 patients with recurrent kidney stones, as well as 54 controls, also indicated that patients with recurrent kidney stones had signi cantly lower bone mineral density [18]. According to a study that grouped patients with urolithiasis by age, osteoporosis incidence increased with age [19]. Carbone et al 7 present a different perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 57 patients with recurrent kidney stones, as well as 54 controls, also indicated that patients with recurrent kidney stones had signi cantly lower bone mineral density [18]. According to a study that grouped patients with urolithiasis by age, osteoporosis incidence increased with age [19]. Carbone et al 7 present a different perspective.…”
Section: Discussionmentioning
confidence: 99%
“…New studies by multiple regression show signifi cant impact of age and daily calcium intake on bone mass loss in urolithiasis patients. Signifi cantly reduced bone mass was found in urolithiasis patients compared to control group, and it was more prevalent in older population, especially women in menopause (19).…”
Section: Age and Sexmentioning
confidence: 92%
“…20 % of calcium stone formers have osteopenia and 7 % osteoporosis. Although normal DXA declines with increasing age, osteoporosis is more prevalent and more pronounced in older patients (over 60 years of age) with nephrolithiasis (Bijelic et al 2016). On the other hand, Sakhaee et al (2017) did not find any association between urine calcium and BMD in patients with calcium nephrolithiasis in a large group of males and estrogen treated females.…”
Section: Calcification Processes As a Potential Cause Of Osteopenia/omentioning
confidence: 97%